Work Efforts in the Context of Improving the Performance of Education Personnel at Universitas Negeri Padang - Nella Nella; Sufyarma M; Sulastri Sulastri (Postgraduate School, Universitas Negeri Padang, 2022)
The main purpose of this research is to identify and acquire the necessary information regarding the work effort in improving employee's job performance. The research was conducted at Universitas Negeri Padang in October 2022. The method is a survey with a questionnaire as a tool for data collection. This research included 40 employees as a unit analysis. The data is analyzed using a descriptive approach. The results indicate that Universitas Negeri Padang employees have high work effort and performance. Those findings show that high work effort has affected employees' performance at Universitas Negeri Padang. Therefore, the employee's job performance should be kept by giving rewards. It should be put into the account of maintaining employees at Universitas Negeri Padang.